MODELLING SYNERGISTIC EYE MOVEMENTS IN THE VISUAL FIELD - BARITZ Mihaela; BRAUN Barbu (Journal of Industrial Design and Engineering Graphics, 2015)
Some theoretical and practical considerations about eye movements in visual field are presented in the first part of this paper. These movements are developed into human body to be synergistic and are allowed to obtain the visual perception in 3D space. The theoretical background of the eye movements’ analysis is founded on the establishment of movement equations of the eyeball, as they consider it a solid body with a fixed point. The exterior actions, the order and execution of the movements are ensured by the neural and muscular external system and thus the position, stability and movements of the eye can be quantified through the method of reverse kinematic. The purpose of these researches is the development of a simulation model of human binocular visual system, an acquisition methodology and an experimental setup for data processing and recording regarding the eye movements, presented in the second part of the paper. The modeling system of ocular movements aims to establish the binocular synergy and limits of visual field changes in condition of ocular motor dysfunctions. By biomechanical movements of eyeball is established a modeling strategy for different sort of processes parameters like convergence, fixation and eye lens accommodation to obtain responses from binocular balance. The results of modelling processes and the positions of eye ball and axis in visual field are presented in the final part of the paper.